Integration of project based learning models with interactive multimedia: Innovative efforts to improve student breaststroke swimming skills - Mashud; Syamsul Arifin; Advendi Kristiyandaru; Y Touvan Juni Samodra; I Gusti Putu Ngurah Adi Santika; Didi Suryadi (Physical Education of Students, 2023)
Background and Study Aim. Breaststroke swimming is one of the compulsory subjects for students majoring in sports education at Lambung Mangkurat University. Thus, it is important to have good breaststroke swimming skills so that later it will become the basis for creating experienced and potential teachers. Therefore, there is a need for special treatment to improve breaststroke swimming skills. This study aims to provide evidence of the integration of project based learning models with interactive multimedia on improving students' breaststroke swimming skills.